EPHA2 Receptor as a Possible Therapeutic Target in Viral Infections - Vincenzi, Marian; Mercurio, Flavia A.; Leone, Marilisa (Current Medicinal Chemistry, 2024)
Background: The receptor tyrosine kinase EphA2 plays a role in many diseases, like cancer, cataracts, and osteoporosis. Interestingly, it has also been linked to viral infections. Objective: Herein, current literature has been reviewed to clarify EphA2 functions in viral infections and explore its potential role as a target in antiviral drug discovery strategies. Methods: Research and review articles along with preprints connecting EphA2 to different viruses have been searched through PubMed and the web. Structures of complexes between EphA2 domains and viral proteins have been retrieved from the PDB database. Results: EphA2 assumes a key role in Kaposi’s sarcoma-associated herpesvirus (KSHV) and Epstein Barr virus (EBV) infections by directly binding, through its ligand binding domain, viral glycoproteins. For human cytomegalovirus (HCMV), the role of EphA2 in maintaining virus latency state, through cooperation with specific viral proteins, has also been speculated. In certain cells, with high EphA2 expression levels, following ligand stimulation, receptor activation might contribute to severe symptoms accompanying a few viral infections, including lung injuries often related to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Conclusion: Since EphA2 works as a host receptor for certain viruses, it might be worth more deeply investigating known compounds targeting its extracellular ligand binding domain as antiviral therapeutics. Due to EphA2's function in inflammation, its possible correlation with SARS-CoV-2 cannot be excluded, but more experimental studies are needed in this case to undoubtedly attribute the role of this receptor in viral infections.
Keywords: ephrin